2017
DOI: 10.3389/fpls.2017.00317
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes Associated with Boron Deficiency in Leaves of Two Citrus Scion-Rootstock Combinations

Abstract: Boron (B) deficiency stress is frequently observed in citrus orchards and causes considerable loss of productivity and fruit quality. Carrizo citrange (Cc) has been reported as a rootstock more tolerant to B deficiency than Trifoliate orange (To). The ‘Newhall’ navel orange (Ns) performed better when grafted onto Cc (Ns/Cc) than when grafted onto To (Ns/To) under long-term B deficiency. The present study confirmed that Ns/Cc had higher boron content, leaf fresh weight, lower leaf chlorosis and stronger photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…However, no significant difference of chlorophyll a, b and a + b was found in rootstock grafted cucumber compared to control. The result indicated grafting onto figleaf gourd regulated the reduction of Chl accumulation in cucumber leaves, which are consistent with the results obtained by [30]. Furthermore, the transcriptome data showed that the expression levels of Chl synthesis-related genes were significantly down-regulated in NG while they were not or slightly down-regulated in RG cucumber when compared to respective control (Table S10).…”
Section: Discrepancy Of Morphology and Photosynthesis Between Ng And supporting
confidence: 87%
See 1 more Smart Citation
“…However, no significant difference of chlorophyll a, b and a + b was found in rootstock grafted cucumber compared to control. The result indicated grafting onto figleaf gourd regulated the reduction of Chl accumulation in cucumber leaves, which are consistent with the results obtained by [30]. Furthermore, the transcriptome data showed that the expression levels of Chl synthesis-related genes were significantly down-regulated in NG while they were not or slightly down-regulated in RG cucumber when compared to respective control (Table S10).…”
Section: Discrepancy Of Morphology and Photosynthesis Between Ng And supporting
confidence: 87%
“…However, after grafted onto figleaf gourd, photosynthetic parameters of cucumber leaf, with the exception of Gs, exhibited steady state. A similar report of grafting triggering stronger photosynthetic ability was found in citrus under abiotic stress [30]. All of 14 DEGs encoded chlorophyll a-b binding protein were down-regulated in NG while two of them were down-regulated in RG, and the rate of descent was lower in RG than NG (Table S10).…”
Section: Discrepancy Of Morphology and Photosynthesis Between Ng And supporting
confidence: 74%
“…It was shown that, lignin accumulated when sugar was in rapid decrease in the peach endocarp, indicating that lignin accumulation was in association with the declined sugar content, which accelerated the pit hardening process [26]. Other studies showed that total soluble sugar content increased significantly as well as lignin, and genes related to glucose and lignin synthesis were strongly induced by boron deficiency stress in leaves of citrus [27]. The possible link between lignin accumulation with sugar metabolism was reinforced by the observation that sugars availability positively affected the cell wall biosynthesis, which included lignin synthesis in Arabidopsis thaliana [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the main function of this micronutrient is its structural role in the cell wall where borate forms a diester bond between apiose residues of two rhamnogalacturonan II monomers, providing an enhanced firmness to the cell wall [19,20]. Moreover, B deprivation does not only affect the cell wall but also disturbs many metabolic and physiological processes such as membrane and cytoskeleton structure and function, oxidative stress and secondary metabolism, nitrogen assimilation, and gene expressions, among others [14,18,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%